Upconversion photoluminescence in poly(ladder-type-pentaphenylene) doped with metal (II)-octaethyl porphyrins - Baluschev, S.; Keivanidis, Panagiotis E.; Wegner, G.; Jacob, J.; Grimsdale, A. C.; Müllen, K.; Miteva, T.; Yasuda, A.; Nelles, G. (My University, 2005)
We report on the optimization of the upconversion photoluminescence in films of conjugated polymers doped with platinum porphyrin. The upconversion emission was observed to take place at pump intensities as low as 0.5 kWcm2. Comparison between the photoluminescence integral intensity of polyfluorene and ladder-type pentaphenylene polymer shows a five-fold increase of the efficiency of the upconversion process for the latter. The higher upconversion efficiency can be partially attributed to the reduced reabsorption of the photoluminescence in the case of the ladder-type pentaphenylene matrix. © 2005 American Institute of Physics.
Keywords: Absorption; Doping (additives); Optimization; Photoemission; Photoluminescence; Platinum compounds; Porphyrins